Analisis Yuridis Pemerasan dan Pengancaman di Pasar Baru Atambua - Stella Gratio Jehaman; Rudepel Petrus Leo; Bhisa Vitus Wilhelmus (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to identify the reasons behind the recurring commission of extortion and criminal intimidation at Pasar Baru Atambua despite these acts being regulated under Articles 482 and 483 of the New Criminal Code and to determine whether law enforcement processes align with applicable regulations. The study employs an empirical-juridical method, utilizing both statutory and field-based approaches. Data were gathered through literature reviews and interviews with relevant stakeholders at Pasar Baru Atambua and the Belu District Police (Polres Belu). The findings indicate that extortion and intimidation persist at Pasar Baru Atambua due to victims' reluctance to report incidents, a prevalence of non-formal resolutions or restorative justice, and a lack of effective deterrence for perpetrators. The study also reveals that law enforcement has not fully adhered to the provisions of Articles 482 and 483 of the New Criminal Code; among the incidents that occurred, only the